Polymerization of -pinene with ethylaluminum dichloride (C2H5AlCl2). - Guiné, Raquel (2013)
The main goal of this work is to study the cationic polymerisation of terpenes, particularly of -pinene, with alkylaluminium catalysts. Some experiments at different polymerisation temperatures (10, 20 and 50ºC) were carried out with ethylaluminium dichloride catalyst, C2H5AlCl2. From the results, it is possible to draw some general conclusions about the evolution of chain growth during polymerisation. This also includes the influence of reaction temperature upon some properties of the final resin, particularly the molecular weight distribution, the softening point and the Gardner colour index. The role of reducing agents, such as iodine, during the distillation of the final resin is also evaluated with respect to colour and softening point. As a result of this investigation, the Mark-Howink constants for terpene resins in toluene and dicloromethane as solvents have also been experimentally determined, thus allowing a more precise use of SEC in the characterisation of such natural based products.